2011
DOI: 10.1007/s13361-011-0176-y
|View full text |Cite
|
Sign up to set email alerts
|

N-Centered Odd-Electron Ions Formation from Collision-Induced Dissociation of Electrospray Ionization Generated Even-Electron Ions: Single Electron Transfer via Ion/Neutral Complex in the Fragmentation of ProtonatedN,N′-Dibenzylpiperazines and ProtonatedN-Benzylpiperazines

Abstract: Single electron transfer (SET) via ion/neutral complex (INC) was proposed and confirmed to be the key step in the formation of N-centered odd-electron ions from fragmentation of protonated even-electron ions in the present study. Upon collisional activation, the model compounds, protonated N,N′-dibenzylpiperazine and protonated N-benzylpiperazines initially dissociated to form intermediate INCs consisting of N-benzylpiperazine (or piperazine) and benzyl cation. In these ion/neutral complexes, SET reaction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…The applications of electron ionization and electrospray ionization (ESI) mass spectrometry to various substituted triazines are well known in the literature . Tandem mass spectrometric experiments have shown that the dissociation of protonated molecules containing more than one benzyl groups yield product ion of m/z 181 having molecular formula C 14 H 13 + due to benzyl‐benzyl interactions . Examples include study of the protonated dibenzyl esters of dicarboxylic acid generated by chemical ionization and N , N ′‐dibenzylpiperzines produced by ESI .…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The applications of electron ionization and electrospray ionization (ESI) mass spectrometry to various substituted triazines are well known in the literature . Tandem mass spectrometric experiments have shown that the dissociation of protonated molecules containing more than one benzyl groups yield product ion of m/z 181 having molecular formula C 14 H 13 + due to benzyl‐benzyl interactions . Examples include study of the protonated dibenzyl esters of dicarboxylic acid generated by chemical ionization and N , N ′‐dibenzylpiperzines produced by ESI .…”
Section: Introductionsupporting
confidence: 73%
“…The proposed mechanism for the benzyl–benzyl interactions involves ion/neutral complexes (INCs) based on experimental data. Recently DFT calculations, using B3LYP/6‐31G(d) level of theory, have been utilized to substantiate the involvement of INCs . The 2,4,6‐tris(benzylamino)‐ s ‐triazines ( 1–5 ) and 2,4,6‐tris(benzyloxy)‐ s ‐triazines ( 6 and 7 ) offers a unique opportunity to investigate the gas‐phase behavior of compounds containing three benzyl groups and to compare the dissociations of compound in which the benzyl groups are attached to N‐atom and O‐atom.…”
Section: Introductionmentioning
confidence: 99%
“…The ionic and neutral components of an INC show reactivities similar to those expected for the isolated species in the bimolecular reactions. In previous studies, we found dissociation of protonated N-benzyl amines gave rise to [benzyl cation/amine] complex and then nucleophilic aromatic substitution [8], electron transfer [23], or hydride transfer [24] could occur within the complex in different cases. In the present study, we systematically investigated the gas-phase reactions of benzyl cations with neutral N-containing species through INC intermediates in collision-induced dissociation of N-benzylated cations in ESI-MS. With these efforts, we try to figure out a more integrated landscape of the gas-phase reactivity of benzyl cations.…”
Section: Introductionmentioning
confidence: 98%
“…In electrospray ionization mass spectrometry (ESI-MS), fragmentation of benzylated cations prefers to generate benzyl cations [7,8,[20][21][22][23][24][25][26][27][28][29][30], though a few exceptions have been reported that tropylium ion can be co-produced in the fragmentation of benzylpyridinium ions [18,31,32]. Besides the formation of benzyl cations, other interesting ions resulting from hydride transfer [24,25] or electrophilic aromatic substitution reactions [20][21][22] via the nonconventional ion/neutral complex (INC) can also be generated in the dissociation of benzylated cations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation